2010
DOI: 10.1017/s0031182010000764
|View full text |Cite
|
Sign up to set email alerts
|

Newly defined conditions for thein vitrocultivation and cryopreservation ofDientamoeba fragilis: new techniques set to fast track molecular studies on this organism

Abstract: Dientamoeba fragilis is a pathogen of the human gastrointestinal tract that is a common cause of diarrhoea. A paucity of knowledge on the in vitro cultivation and cryopreservation of Dientamoeba has meant that few studies have been conducted to investigate its biology. The objective of this study was to define, for the first time, in vitro culture conditions able to support the long-term in vitro growth of Dientamoeba. Also, we aimed to define a suitable method for cryopreserving viable Dientamoeba trophozoite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 32 publications
(79 reference statements)
0
41
0
2
Order By: Relevance
“…Barratt et al (33) describe phenotypic differences between the in vitro growth characteristics of different clinical D. fragilis isolates and suggested that they might have a genetic basis. All D. fragilis isolates included in the study by Barratt et al (33) were confirmed to be genotype 1 isolates, so any potential genetic diversity must exist in other genes.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Barratt et al (33) describe phenotypic differences between the in vitro growth characteristics of different clinical D. fragilis isolates and suggested that they might have a genetic basis. All D. fragilis isolates included in the study by Barratt et al (33) were confirmed to be genotype 1 isolates, so any potential genetic diversity must exist in other genes.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Microscopy of fixed smears with permanent staining (modified iron-hematoxylin or trichrome staining) (127,393,403) is considered the gold standard for diagnosis of D. fragilis infection, but this method is timeconsuming and relatively insensitive compared to molecular methods (391). More recently, diagnostic tests based on various conventional and real-time PCRs to detect the small-subunit (SSU) rRNA gene of D. fragilis have been developed to facilitate rapid, sensitive, and specific diagnosis in fresh stools (386,388,401,455), and the successful culture and cryopreservation of viable D. fragilis trophozoites from clinical specimens have been achieved (27,355). It was demonstrated that when microscopy is combined with other methods, the success of detection of D. fragilis is increased significantly (26,386,388).…”
Section: Dientamoeba Fragilismentioning
confidence: 99%
“…The approach to in vitro culture is not new; however, some excellent improvements have recently been developed (39,40). Currently, no axenic cultures of D. fragilis exist.…”
Section: Diagnosismentioning
confidence: 99%
“…A temperature of 42°C and a microaerophilic atmosphere are also optimum for growth. Compared to other media, Loeffler's slope medium led to much better growth of D. fragilis (40). A modified Earle's balanced salt solution containing cholesterol, ferric ammonium citrate, and rice starch is considered a superior liquid overlay that can be used along with Loeffler's serum slope for culture of D. fragilis under anaerobic conditions.…”
Section: Diagnosismentioning
confidence: 99%